Optimization of Water Utilization for Irrigation Networks (Case Study: Wawotobi Dam, Unaaha District, Konawe Regency) - Arman Hidayat; Fathur Rahman Rustanto; Gunawansyah Gunawansyah; Faisal Cahyadi Saima (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Water is a very important natural resource. Water is needed for industrial, agricultural, fishery or pond activities, and other businesses. Planning and management of irrigation systems is one of the important stages to determine the overall demand for irrigation water.The Wawotobi Irrigation Area (DI) is the largest irrigation area in Southeast Sulawesi. Currently, this high water loss can lead to unfulfilled water needs in irrigated gardens, resulting in failure at harvest. This research was conducted by calculatingmainstay discharge to supply irrigation water needs,plan for cropping patterns in the irrigation area of the Wawotobi weir, Konawe Regency.This study also analyzes channel efficiency in the Wawotobi irrigation network by conducting field observations. The data from the observations are then analyzed so that it can be seen how much efficiency is in the distribution of irrigation water. In addition, this research also analyzes the water balance so that alternatives can be given in an effort to optimize the operation of water distribution in the irrigation network. Based on the analysis that has been done using the rice-paddy-palawija cropping pattern, the results of the calculation of the maximum water demand on the BW1 – B Un irrigation network are obtained. 5 Tg during the existing growing season was 9,477 L/sec, During the first growing season it was 9.998 L/sec, During the second growing season it was 7,452 L/second At the third growing season it was 9.998 L/second with a water balance rate which is quite high, namely 17.17 during land preparation. Irrigation network BW1 – B Un. 5 Tg has a network efficiency of 80%, which meets the irrigation planning standards of 80-90%.